Discourse and social practices of sustainability in Brazilian cattle ranching - Claudino, Livio Sergio Dias (Sustainability in Debate, 2014)
The issue of sustainability is very comprehensive, multifaceted and controversial, especially when it assumes the existence of differences on their meanings, how to practice it, or even if it materializable or just ideology. Viewpoints and different approaches points lead to different mechanisms for the operation and the consequent different results sustainability. This text aims to analyze the discursive and practices associated with the notion of sustainability in the context of the Brazilian cattle breeding. The article is based on literature from different sources, from theoretical articles, from the environment conference reports to technical texts and case studies relating to livestock and environmental impacts. Was evidenced technocratic institutionalization of "strategic models" called "sustainable livestock", which are distinct from each other, nature and form, and especially the priorities and execution mechanisms.